Faktor-Faktor Yang Berhubungan Dengan Perilaku Konsumsi Makanan Pada Peserta Didik SD Swasta Kartika I-1 Medan - Sri Lasmawanti; Dedi Dedi; Maria Haryanti Butarbutar; Agnesia Sitohang (Jurnal Medika Nusantara, 2023)
Snacking is one of the activities of children in the school environment. The purpose of this study was to determine whether there was a Relationship between Knowledge, Peer Influence, Advertising, and Snacking Behavior in Private Elementary School Students Kartika I-1. The research design used in this study used an Analytical Survey method with a cross-sectional approach. This research was conducted at Kartika I-1 Private Elementary School. The population in this study were elementary school students totaling 250 respondents. The sampling technique was by purposive sampling using the Slovin formula, namely 71 people. The data collection instrument used a questionnaire that was distributed directly to the respondents. Data were analyzed using univariate and bivariate analysis using chi-square test. Based on the results of the study with chi-square test on knowledge with snacking behavior obtained p-value = 0.003, peer influence p-value = 0.004, advertisement p-value = 0.003. The conclusion is that there is a significant relationship between knowledge, peer influence, advertising, and snacking behavior in Kartika I-1 Private Elementary School students. It is suggested to parents to participate and increase their role as parents who can provide knowledge and motivation to maintain the health of their children and also to teachers need to also teach what snacks should be consumed by children.